Phosphorus size-distribution and cycling in the plankton of two oligotrophic lakes with contrasting fish communities - Hudson, Jeffrey James (University of Waterloo, 1997)
The effect of food web structure on phosphorus (P) cycles in two oligotrophic lakes was investigated. In 1993, Mouse Lake contained planktivorous fish, while Ranger Lake contained piscivorous and planktivorous fish. In late 1993 and early 1994, the majority of piscivores were removed from Ranger and placed in Mouse L. Total P (TP) concentrations changed slightly in Mouse Lake; TP was higher when planktivorous fish were abundant. TP declined during summer stratification each year, but the rate of decline was unaffected by treatment. Meso- and nanoplankton size fractions of P responded inversely to each other in Ranger L., but not in Mouse L. The size-distribution of particulate P (PP) did not respond to treatment. Turnover time of PO4^-3 did not respond to treatment and was always rapid. However, PO4^-3 concentrations and uptake velocities showed a weak response, particularly in Mouse L.; PO4^-3 and uptake velocities were greater when piscivores were abundant. By comparison with regeneration rates, ambient uptake and PO4^-3 concentrations appeared to be overestimated by the modified Rigler radiobioassay. A technique was developed to measure release of dissolved phosphorus (DP) from plankton communities. Plankton are radiolabeled with phosphate and then re-assimilation is competitively blocked with 31PO4^-3. The increase in dissolved radioactivity is then assayed. Initial ratio of 31P to radioactivity and increase in dissolved radioactivity are used to estimate release of DP. Mean epilimnetic regeneration was 41 ng P 1^-1 h^-1 and mean turnover time of TP was 7 days. The size fraction less than 40 um accounted for 78% of total regeneration. Protists and bacteria appear to be the major regenerators of phosphorus in the plankton of these lakes. Total P regeneration and specific regeneration were greatest when piscivores were abundant. Zooplankton (>40 um) regeneration and specific regeneration were also greatest when piscivores were abundant. Protist (o.8-40 um) regeneration and specific regeneration responded to treatment in Ranger L., but not in Mouse L. Bacterial rates (<0.8 um) did not respond to treatment. Zooplankton and protists rates were often inversely related. Phosphorous regeneration does not seem to be the primary mechanism structuring the pelagic communities in these biomanipulated lakes.
Keywords: Harvested from Collections Canada